Inhibition of miR-20a promotes neural stem cell survival under oxidative stress conditions - Arzhanov, Ivan; Klassen, Ruslan A.; Valihrach, Lukas; Romanyuk, Nataliya (Frontiers in Neuroscience, 2025)
IntroductionOxidative stress (OS) is a key contributor to secondary damage following spinal cord injury (SCI), leading to neural stem cell (NSC) dysfunction and apoptosis. MicroRNA-20a (miR-20a) is upregulated after SCI and plays a role in regulating apoptosis and survival pathways. This study explores the therapeutic potential of miR-20a inhibition in mitigating OS-induced damage in NSCs.MethodsHuman iPSC-derived NSCs were subjected to oxidative stress by exposure to 100 µM hydrogen peroxide (H2O2) for 2 hours, followed by treatment with a miR-20a inhibitor (100 nM) to attenuate the adverse effects. Metabolic activity was evaluated using the Alamar Blue assay. Apoptotic responses and miR-20a expression levels were assessed via flow cytometry, RT-qPCR, and Western blot analysis.ResultsNSCs exposed to OS showed a marked reduction in metabolic activity. However, treatment with a miR-20a inhibitor over 72 h significantly improved cell survival and metabolic activity in a time-dependent manner compared to untreated stressed cells.DiscussionOur findings suggest that miR-20a inhibition mitigates OS-induced cytotoxicity and promotes NSC viability, presenting a potential therapeutic approach for enhancing neural tissue regeneration.